2024
DOI: 10.1021/acs.jmedchem.4c00090
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure–Activity Relationship of Novel Pyridazinone-Based PARP7/HDACs Dual Inhibitors for Elucidating the Relationship between Antitumor Immunity and HDACs Inhibition

Ji-Long Duan,
Chen-Chen Wang,
Yinghui Yuan
et al.

Abstract: Histone deacetylases (HDACs) inhibitors such as vorinostat (SAHA) has been used to treat hematologic malignancies (rather than solid tumors) and have been found to suppress the JAK/STAT, a critical signal pathway for antitumor immunity, while PARP7 inhibitor RBN-2397 could activate the type I interferons (IFN-I) pathway, facilitating downstream effects such as STAT1 phosphorylation and immune activation. To elucidate whether simultaneous inhibition of these two targets could interfere with these two signal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…This hypothesis forms the basis for the project we report here. In our ongoing PARP7-related dual inhibitor program, we have observed that the trifluoromethyl pyrimidine side chain could be replaced with a much larger attachment without losing PARP7 activity . We reason that an appropriate linker could be used in this region to attach a PD-L1 small-molecule inhibitor scaffold so that a novel class of bifunctional conjugate targeting PD-L1/PARP7 could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis forms the basis for the project we report here. In our ongoing PARP7-related dual inhibitor program, we have observed that the trifluoromethyl pyrimidine side chain could be replaced with a much larger attachment without losing PARP7 activity . We reason that an appropriate linker could be used in this region to attach a PD-L1 small-molecule inhibitor scaffold so that a novel class of bifunctional conjugate targeting PD-L1/PARP7 could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…These drug targets encompass a range of biomolecules, including proteins, enzymes, cell-membrane receptors, DNA or RNA sequences, and key regulatory factors within cellular signaling pathways or biological processes [ 1 ].The accurate determination of drug targets enables the purposeful design of a series of drugs that have superior therapeutic effects, safety, and applicability. These drugs typically act more precisely on specific parts or mechanisms, thereby demonstrating remarkable curative effects and bringing significant breakthroughs in disease treatment [ 2 , 3 , 4 , 5 ]. In the early stages of drug development, target identification primarily relies on biochemical and molecular biology methods, but these methods are often inefficient and time-consuming.…”
Section: Introductionmentioning
confidence: 99%